1 Esdras : introduction and commentary on the Greek text in Codex Vaticanus - Bird, Michael F. (Septuagint Commentary Series., 2012)
In 1 Edras Michael Bird presents a commentary on this much neglected text based on its witness in Codex Vaticanus as part of the next installment of the Septuagint Commentary Series. Containing material that parallels 2 Chronicles, Ezra, and Nehemiah, 1 Esdras is featured in the Septuagint and Christian Apocrypha. The commentary presents a survey of critical issues related to the study of 1 Esdras and provides an impressive literary analysis of the contours of 1 Esdras.